Hepatitis A Virus Infection in Guillain-Barré Syndrome - Neneng Ratnasari; Siti Nurdjanah (The Indonesian Society for Digestive Endoscopy, 2002)
Prodromal factors of Guillain-Barré syndrome (GBS) are often associated with previous viral infection (60%). The ailment supported by the acquired immunomediated disorder concept. Viral hepatitis is very rarely found in GBS, preceded by cytomegalovirus (15-18%), Campylobacter jejuni (28%), and Epstein-Barr virus (5%). There is no specific etiology of GBS because those viruses usually appear sporadically (subclinically). All hepatitis virus infection can cause neurological complications, including GBS. We report two cases of hepatitis A virus infection (HAV) in GBS patients in Dr. Sardjito General Hospital during 5 years of observation (1996-2000) from 92 GBS patients. The diagnosis of HAV was based on more than 2 times increment of transaminase enzyme, positive IgM anti HAV, negative HbsAg, and negative IgM anti HCV. The diagnosis of GBS was based on clinical symptoms of acute generalized paralysis, cerebrospinal fluid examination, and electromyelography. In both cases, sub-clinical and sporadic symptoms appeared several days before paralysis, which makes it more likely that the prodromal period of GBS occurred at the same time of HAV incubation period.